Heat capacities and thermodynamic functions of new cobalt manganites LaM 2 II CoMnO6 (MII-Mg, Ca, Sr, Ba) in the 298.15–673 K temperature range - Kasenov, B.K.; Turtubaeva, M.O.; Amerkhanova, Sh.K.; Kasenova, Sh.B.; Sagintaeva, Zh.I.; Kuanyshbekov, E.E.; Seisenova, A.A.; Smagulova, D.I. (Pleiades Publishing, 2015)
Temperature dependences of the heat capacities of cobalt manganites LaM 2 II CoMnO6 (MII = Mg, Ca, Sr, Ba) are investigated by means of dynamic calorimetry in the temperature range of 298.15–673 K. It is established that cobalt manganites display λ-like effects on the C p po ∼ f(T) curve, which are likely to be related to the type II phase transitions. Equations for the temperature dependence of the heat capacity of cobalt manganites are derived from the experimental data with allowance for phase transition temperatures. The values of C p po (T) and thermodynamic functions H po(T) − H po(298.15), S po(T), and Φxx(T) are calculated.
Keywords: cobalt manganite; dynamic calorimetry; heat capacity; thermodynamic functions